The introduction of HPV vaccines in Brazil: advances and challenges - Domingues, Carla Magda Allan Santos; Maranhão, Ana Goretti Kalume; Pinto, Michelle Flaviane Soares (Brazilian Journal of Sexually Transmitted Diseases, 2022)
The impact of the human papillomavirus (HPV) infection all over the world is considerable. Its importance as a public health issue is demonstrated by its high frequency, association to uterine cancer (mostly), and clinical implications, besides the psychological impact on the affected people(1). More than one of two women have been exposed to HPV throughout life; 10% have the virus in its chronic form, and, among these, one of five women has a chance of developing uterine cancer without screening tests or in case, the examination is flawed(2,3). It is worth mentioning that uterine cervix cancer usually affects women aged around 40 years, at a time when their family, professional, and social responsibilities are significant(4). [...]